2019
DOI: 10.1080/01900692.2019.1660994
|View full text |Cite
|
Sign up to set email alerts
|

Technology, Education, Life and Non-life Insurance in Africa

Abstract: This article examines the relevance of information and communication technology (ICT) in modulating the effect of education on life insurance and non-life insurance consumption in 48 African countries for the period 2004-2014. Education is measured with primary school, secondary school and tertiary school enrollments. ICT is measured with mobile phone, internet and broadband subscriptions. The empirical evidence is based on generalized method of moments. The following main findings are established. First, from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…Moreover, in this study, the negative relationship between education and the demand for life insurance is highlighted, a fact confirmed also by Beck & Webb (2003). Nevertheless, positive interlinkages between life insurance and education for European (Dragos et al, 2017), South-Asian (Sanjeew et al, 2019 and African countries were revealed when information and communication technology (ICT) was included in the analysis (Asongu, 2020). Thus, expanding the ICT applications will act as a favorable support for life insurance and education.…”
Section: Literature Reviewsupporting
confidence: 50%
See 1 more Smart Citation
“…Moreover, in this study, the negative relationship between education and the demand for life insurance is highlighted, a fact confirmed also by Beck & Webb (2003). Nevertheless, positive interlinkages between life insurance and education for European (Dragos et al, 2017), South-Asian (Sanjeew et al, 2019 and African countries were revealed when information and communication technology (ICT) was included in the analysis (Asongu, 2020). Thus, expanding the ICT applications will act as a favorable support for life insurance and education.…”
Section: Literature Reviewsupporting
confidence: 50%
“…Education has a key role to play in informing the public about the importance, role and use of insurance products, as well as in shaping risk awareness, as suggested by many scholars (Asongu, 2020;Dragos et al, 2017;Hammond et al, 1967;Sanjeew et al, 2019;Strzelecka et al, 2020). Failure to use insurance products and failure to insure risks by the population and companies such as accidents, diseases or natural disasters, would cause shocks in society with serious consequences that may persist over time, on economic growth and human development / quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Prior GMM-centric literature has established five basic justifications for adopting GMM estimator in the literature (Asongu, 2019;Asongu, Adegboye, & Nnanna, 2021;Asongu, Adegboye, Ejemeyovwi, et al, 2021). These factors are discussed with no priority: (i) The number of cross-sections (i.e., N) must exceed the number of corresponding periods.…”
Section: Methodsmentioning
confidence: 99%
“…The educational quality indicator used in the study is the "primary school enrollment, secondary school enrollment and tertiary school enrollment" gender parity indexes. The reasons underpinning the employment of these educational indicators include the lifelong learning motives and the necessity of educational quality in socio-economic development (Asongu, 2020;Asongu, Orim, & Nting, 2019). Moreover, these educational quality variables also double as gender inclusive variables given the relevant feature of gender inclusion in sustainable development goals (SDGs).…”
Section: Datamentioning
confidence: 99%
“…In the light of the attendant literature, data behaviour usually determines the choice of the estimation strategy adopted in a study. The choice of GMM approach builds on five justifications in accordance with contemporary literature (Asongu, 2020) which are discussed in no order of importance. First, the number of the cross sections (i.e.…”
Section: Gmm Specificationmentioning
confidence: 99%